Twos in human visual perception. (November 2020) - Papeo, Liuba
Abstract: Human vision serves the social function of detecting and discriminating with high efficiency conspecifics and other animals. The social world is made of social entities as much as the relations between those entities. Recent work demonstrates that vision encodes visuo-spatial relations between bodies with the same efficiency and high specialization of face/body perception. Specifically, perception of face-to-face (vs. non-facing) bodies evokes effects compatible with the most robust markers of face-specificity such as the behavioral inversion effect and increased activity in selective visual areas. Another set of results suggests that face-to-face bodies are processed as a grouped unit, analogously to facial features in a face. The facing dyad in the visual cortex may be the earliest rudimentary representation of social interaction.